Therapeutic approach and outcome of children with Philadelphia chromosome‐positive acute lymphoblastic leukemia at first relapse in the era of tyrosine kinase inhibitors: An SFCE retrospective study. Issue 2 (2nd December 2021) - Aubert, Lucie; Petit, Arnaud; Bertrand, Yves; Ray‐Lunven, Anne‐France; Angoso, Marie; Pluchart, Claire; Millot, Frédéric; Saultier, Paul; Cheikh, Nathalie; Pellier, Isabelle; Plantaz, Dominique; Sirvent, Anne; et al.
Abstract: Background: Since the introduction of tyrosine kinase inhibitors (TKIs), the profile of pediatric relapse of Philadelphia chromosome‐positive acute lymphoblastic leukemia (Ph + ALL) has changed. However, the management of pediatric Ph + ALL relapses is not currently standardized. Procedure: We retrospectively analyzed the therapeutic strategies and outcomes of pediatric Ph + ALL patients in first relapse who were initially treated with a TKI‐containing regimen in one of the French pediatric hematology centers from 2004 to 2019. Results: Twenty‐seven children experienced a Ph + ALL relapse: 24 (89%) had an overt relapse and three a molecular relapse. Eight involved the central nervous system. A second complete remission (CR2) was obtained for 26 patients (96%). Induction consisted of nonintensive chemotherapy for 13 patients (48%) and intensive chemotherapy for 14 (52%). Thirteen patients (48%) received consolidation. Allogenic hematopoietic stem cell transplantation (alloHSCT) was performed for 21 patients (78%). The TKI was changed for 23 patients (88%), mainly with dasatinib ( n = 15). T315I was the most common mutation at relapse (4/7). The 4‐year event‐free survival and survival rates were 60.9% and 76.1%, respectively. Survival was positively associated with alloHSCT in CR2. Conclusion: We show that pediatric first‐relapse Ph + ALL reinduces well with a second course of TKI exposure, despite the use of different therapeutic approaches. The main prognostic factor for survival was alloHSCT in CR2. Because of the small size of the cohort, we could not draw any conclusions about the respective impact of TKIs, but the predominance of the T315I mutation should encourage careful consideration of the TKI choice.